Biological systematics history and theory - Pavlinov, I. I︠A︡. (Igorʹ I︠A︡kovlevich) (Species and systematics, 2021)
"This volume reviews the historical roots and theoretical foundations of biological systematics in an approachable text. The author outlines the structure and main tasks of systematics. Conceptual history is characterized as a succession of scientific revolutions. The philosophical foundations of systematic research are briefly reviewed as well as the structure and content of taxonomic theories. Most important research programs in systematics are outlined. The book includes analysis of the principal problematic issues as 'scientific puzzles' in systematics. This volume is intended for professional taxonomists, biologists of various specialties, students, as well as all those interested in the history and theory of biology and natural sciences."--Back cover.